194k views
1 vote
0.2(3k+1)=-0.4-(-0.2-0.1K)

1 Answer

3 votes

Answer:

k=−0.8

Explanation:

Start with the equation: 0.2(3k+1)=-0.4-(-0.2-0.1K)

Use distributive property on each side of the equation. For the left side, distribute 0.2 into 3k and 1, and for the right side, distribute -1 into -0.2 and -0.1k. (We use a -1 because the negative sign on the outside of the parenthesis is equivalent to -1)

(0.2)(3k) + (0.2)(1) = 0.6k + 0.2

(-1)(-0.2) + (-1)(-0.1k) = 0.2 + 0.1k

New equation: 0.6k + 0.2 = -0.4 + 0.2 + 0.1k

Now we can combine like terms on the right side. (-0.4 and 0.2)

0.6k + 0.2 = 0.1k - 0.2

Now to get rid of k on one side, we can subtract 0.1k from the right side.

(0.6k - 0.1k) + 0.2 = (0.1k - 0.1k) - 0.2

0.5k + 0.2 = -0.2

Now we need to get 0.5k by itself, so we'll subtract the 0.2 on both sides.

0.5k + (0.2 - 0.2) = (-0.2 - 0.2)

0.5k = -0.4

To get k by itself, we must divide both sides by 0.5.

(0.5k / 0.5) = (-0.4 / 0.5)

k = -0.8

User Diogo Raminhos
by
4.3k points